2017
DOI: 10.1242/dev.143701
|View full text |Cite
|
Sign up to set email alerts
|

Stomach curvature is generated by left-right asymmetric gut morphogenesis

Abstract: Left-right (LR) asymmetry is a fundamental feature of internal anatomy, yet the emergence of morphological asymmetry remains one of the least understood phases of organogenesis. Asymmetric rotation of the intestine is directed by forces outside the gut, but the morphogenetic events that generate anatomical asymmetry in other regions of the digestive tract remain unknown. Here, we show in mouse and Xenopus that the mechanisms that drive the curvature of the stomach are intrinsic to the gut tube itself. The left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Previous studies have shown that Pitx2 plays two important roles during organogenesis; the left-sided expression in the lateral plate mesoderm is important for overall embryonic left-right determination, while the asymmetric (left side) expression within individual organ's tissues (particularly gut and heart) guides asymmetric morphogenesis of these organs ( Campione et al, 1999 ; Davis et al, 2017 ). Studies (both in mouse and Xenopus ) ( Clauss and Kaab, 2011 ; Davis et al, 2017 ; Poelmann et al, 2008 ) have shown that eliminating asymmetric Pitx2 expression within organs like heart and gut disrupts asymmetric organ morphogenesis and also leads to disrupted organ morphologies. In our studies, the reduced (but correctly-sided) Pitx2 signal in the lateral plate mesoderm may be affecting the Pitx2 expression in the heart and gut organs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Pitx2 plays two important roles during organogenesis; the left-sided expression in the lateral plate mesoderm is important for overall embryonic left-right determination, while the asymmetric (left side) expression within individual organ's tissues (particularly gut and heart) guides asymmetric morphogenesis of these organs ( Campione et al, 1999 ; Davis et al, 2017 ). Studies (both in mouse and Xenopus ) ( Clauss and Kaab, 2011 ; Davis et al, 2017 ; Poelmann et al, 2008 ) have shown that eliminating asymmetric Pitx2 expression within organs like heart and gut disrupts asymmetric organ morphogenesis and also leads to disrupted organ morphologies. In our studies, the reduced (but correctly-sided) Pitx2 signal in the lateral plate mesoderm may be affecting the Pitx2 expression in the heart and gut organs.…”
Section: Discussionmentioning
confidence: 99%
“…The break in symmetry is observed simultaneously at different orientations relative to the dorsal mesentery along the length of the developing intestine (Figure D‐D″). Thus, while the asymmetric morphology is reminiscent of that seen in the generation of the stomach curvature, it is not clear whether this asymmetry is related to left‐right (LR) identity …”
Section: Discussionmentioning
confidence: 99%
“…Thus, while the asymmetric morphology is reminiscent of that seen in the generation of the stomach curvature, it is not clear whether this asymmetry is related to left-right (LR) identity. 32 Naïve cells make up the epithelium and mesenchyme suggesting a rapid growth phase of the gut tube at this stage. Indeed, this rapid growth phase is reflected by the 4.5 spiral rotations seen at stage 27 ( Figure 2F).…”
Section: Initiation Of a Spiralmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, some asymmetries at the level of the stomach appear to rely more on endoderm-intrinsic mechanisms. For instance stomach curvature in mouse and Xenopus relies on asymmetries of tissue architecture and epithelial polarity of cells of the stomach itself, where Pitx2 is expressed in the left stomach wall only [30]. …”
Section: Asymmetric Morphogenesis Of the Organsmentioning
confidence: 99%